A light and electron microscopic study of the liver in case of erythrohepatic protoporphyria and in griseofulvin-induced porphyria in mice. Issue 9 (September 1974) - Matilla, A.; Molland, Elizabeth A.
Abstract : The light- and electron-microscopic appearances of a liver biopsy from a case of erythrohepatic protoporphyria are compared with the appearances of the liver in griseofulvin-induced porphyria in mice. Crystals are present in hepatocytes and in the bile secretory pathways in each case. The nature and significance of these is discussed.